Moins de rhétorique régionale, plus de diversité. L’urbanisation des Alpes dans l’intérêt de sociétés cohésives - Manfred Perlik (Revue de Géographie Alpine)
The current regional development strategies require mountain regions to specialise in their landscape resources and to value them independently. The hypothesis is that this strategy has to be questioned in view of increasing spatial inequality in Europe. In the peripheral areas, this inequality is mainly due to differences in development opportunities. It finds its expression in an increasing social cleavage, which in turn is expressed in polarized voting practices of the population: Rich regions are acting regionalist in order to leave the larger community of solidarity of the nation state. Poor regions see nationalist and openly racist currents spreading. Cities, including those in the Alps, attract an educated and more prosperous population and are able to handle social conflicts more generously. The gap between the large core cities and their hinterlands is widening. In the interest of cohesive societies, it does not seem very expedient in this situation to further intensify regional competition by selectively valorising landscape resources. On the one hand, not all regions are in a position to do so. On the other hand, the valorisation of landscape resources, especially in the Alps, means that it must be profitable for their inhabitants so that they do not out-migrate. However, average benefits are only achievable through large economic structures. In turn, they fuel global mobility, are problematic for ecological reasons and often exclude the local population from use. The current division of European societies confirms the historical work on the resource character of social relations (Bourdieu's concept of capital, interpreted as territorial capital) and the positive effect of many but flat lines of conflict in a society (Rokkan's cross-cutting cleavages). In this light, the focus of regional development on a narrowly defined Alpine identity, which refuses to serve the interests of the neighbouring metropolitan regions, appears increasingly counterproductive. On the one hand, because it cancels out the many conflicts in favour of one single deep conflict between extra-Alpine metropolitan regions and an alpine pseudo-rurality, and on the other hand, because it cuts off the peripheral regions from external knowledge, which they need if they want to be "sustainable". Social innovations, which are particularly important for sparsely populated regions, only arise if there is an open mind towards external knowledge in addition to regional self-confidence. This is the only way to defend structures and ways of life worth preserving against the majority of the population living outside the Alps. The concept of European macro-regions could offer a way out of the tension between identity and openness, provided that these macro-regions seriously attempt to bridge prosperity trenches and national borders with their geographically wide demarcation. In order to do so, they need sufficient competence and the willingness to shape the relationship between the Alps and the plain in such a way that the interests to work and live in the mountain regions under the special conditions of topography are protected. This will not be possible without cross-subsidisation; to achieve this, mountain areas will have to some extent respond to the needs of urban areas. The task remains to renegotiate relations between the Alps and the plains in order to redefine complementarity between them on the basis of a new territorial solidarity.